Estimating time-to-contact with temporal occlusion in relay swimming: a pilot study - Ribeiro, L.; Costa, A. M.; Louro, H.; Sobreiro, P.; Esteves, P.; Conceição, A. (European Journal of Sport Science, 2020)
The purpose of this study was to analyse swimmers` perceptual judgements of a simulated time-to-contact task in freestyle swimming relays.